Synergistic Role of Plant Extracts and Essential Oils against Multidrug Resistance and Gram-Negative Bacterial Strains Producing Extended-Spectrum β-Lactamases - Manzar Alam; Nilofer Bano; Taufeeq Ahmad; Amit Baran Sharangi; Tarun Kumar Upadhyay; Yasser Alraey; Nadiyah M. Alabdallah; Mohd Ahmar Rauf; Mohd Saeed (MDPI AG, 2022)
Plants, being the significant and natural source of medication for humankind against several ailments with characteristic substances hidden on them, have been recognized for many centuries. Accessibility of various methodologies for the revelation of therapeutically characteristic items has opened new avenues to redefine plants as the best reservoirs of new structural types. The role of plant metabolites to hinder the development and movement of pathogenic microbes is cherished. Production of extended-spectrum β-lactamases is an amazing tolerance mechanism that hinders the antibacterial treatment of infections caused by Gram-negative bacteria and is a serious problem for the current antimicrobial compounds. The exploration of the invention from sources of plant metabolites gives sustenance against the concern of the development of resistant pathogens. Essential oils are volatile, natural, complex compounds described by a solid odor and are framed by aromatic plants as secondary metabolites. The bioactive properties of essential oils are commonly controlled by the characteristic compounds present in them. They have been commonly utilized for bactericidal, virucidal, fungicidal, antiparasitic, insecticidal, medicinal, and antioxidant applications. Alkaloids are plant secondary metabolites that have appeared to have strong pharmacological properties. The impact of alkaloids from Callistemon citrinus and Vernonia adoensis leaves on bacterial development and efflux pump activity was assessed on Pseudomonas aeruginosa. Plant-derived chemicals may have direct antibacterial activity and/or indirect antibacterial activity as antibiotic resistance modifying agents, increasing the efficiency of antibiotics when used in combination. The thorough screening of plant-derived bioactive chemicals as resistance-modifying agents, including those that can act synergistically with antibiotics, is a viable method to overcome bacterial resistance. The synergistic assessment studies with the plant extract/essential oil and the antibiotic compounds is essential with a target for achieving a redesigned model with sustainable effects which are appreciably noticeable in specific sites of the plants compared to the entirety of their individual parts.